EDUKASI AGAMA DI ERA DIGITAL: MENINGKATKAN PEMAHAMAN AGAMA ISLAM MELALUI KONTEN YOUTUBE RIKO THE SERIES - Syalla Azzahrra; Selfi Verawati; Alfira Andhini; Rheina Fatimah Azzahra; Muhamad Parhan; Wardani Wardani (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2024)
Religious education in the era of digitalization is very important, especially for young children, to strengthen religious foundations both in terms of worship, faith, and morals. This research aims to analyze, describe, and implement understanding of the Islamic religion through the Riko The Series. This qualitative descriptive research method uses direct observation techniques. The data source for this research is the animated series Riko the Series. Primary data sources were taken from several seasons and episodes of Riko The Series: Season 1 Episode 12, Season 2 Episodes 2, 7, 9, 11, and Season 3 Episode 8. Secondary data sources are books, research journals, or articles related to the topic being researched. Data was collected using note-taking techniques. The results show that Riko the Series is an example of a source of Islamic religious education because it contains educational value in religious character and educational value in faith and morals.